2023
DOI: 10.1186/s12889-023-15003-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on maternal mental health, early childhood development, and parental practices: a global scoping review

Abstract: Background In March 2020, the COVID-19 outbreak was declared a pandemic by the World Health Organization (WHO), generating stark economic and social repercussions that directly or indirectly affected families’ wellbeing and health status. Aims This review aims at mapping the existing evidence on the impact of the COVID-19 pandemic on maternal mental health, early childhood development, and parental practices, worldwide, to identify evidence gaps an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 236 publications
0
8
0
Order By: Relevance
“…Therefore, dysfunctional families are associated with mental distress and harmful parenting behaviors for children. 25 On the contrary, constructive parenting practices are associated with better family dynamics with consequent improvement in child development. Studies have shown that families with better socioeconomic levels have reorganized themselves in order to create a routine in the home environment aiming to reduce the harm in the lives of their children, including the use of the media as a way to promote physical activity in younger children, for example.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dysfunctional families are associated with mental distress and harmful parenting behaviors for children. 25 On the contrary, constructive parenting practices are associated with better family dynamics with consequent improvement in child development. Studies have shown that families with better socioeconomic levels have reorganized themselves in order to create a routine in the home environment aiming to reduce the harm in the lives of their children, including the use of the media as a way to promote physical activity in younger children, for example.…”
Section: Discussionmentioning
confidence: 99%
“…These experiences were both universal ( 25 ) and specific to families of children with autism within the wider parenting experience of caregivers of children with disabilities during the pandemic ( 26 ). Importantly, these shared and unique challenges transcended geographical boundaries and were experienced by several families across low-, middle-and high-income country settings ( 25 , 27 ). We found that the majority of families within our sample received their main financial earnings from private employment or their own businesses both of which were impacted by the lockdown.…”
Section: Discussionmentioning
confidence: 99%
“…Third, this study was limited to the first 2 years of the COVID-19 pandemic. The long-term outcomes of this global disaster are unclear . This investigation supports accounting for timing of the pandemic and the nuances of GWG guidelines based on prepregnancy BMI (ie, less GWG recommended because individuals begin pregnancy heavier).…”
Section: Discussionmentioning
confidence: 99%